Moving images and embodied tourism practices: between propaganda, business and domestic filmmaking - Sampaio, S. (NECS 2017 Conference: "Sensibility and The Senses – Media, Bodies, Practices", 2017)
Travelling has been a driving force in much filmmaking, not least in non-fictional films. From newsreels to utility films and home movies, journeys to faraway places or a simple stroll on the beach have inspired all kinds of ‘other films’. Recent studies on photography and tourism have turned to amateur practices to challenge deterministic views of tourist visuality (most importantly, those associated with the concept of ‘tourist gaze’, coined by British sociologist John Urry – 1990/ 2002). These studies have stressed the performative quality of tourist photography, arguing that it is as much about active ‘framing’ as about passive ‘quotation’ (Larsen 2006). When it comes to the moving image, a similar argument can be made – who would deny that a domestic road movie is a more personal, ‘performed’ experience than a tourism promotional film? Yet, why assume that professional filmmakers are less ‘embodied’ practitioners than amateur filmmakers? Drawing on research conducted at the National Archive of the Moving Images (ANIM) of the Portuguese Film Museum (Cinemateca Portuguesa – Museu do Cinema), which entailed an inventory of tourism-related films as well as interviews with filmmakers, I explore how Portuguese filmmakers active during the 1960s made significant ‘embodied’ options when producing their tourism films. In this process, they had to deal with matters as varied as political propaganda, business strategies and filmmaking practices to create films that (in different measures) should earn the approval of the State, the rising tourism industry, the film milieu and the public.